Analgesic Effects of Lipid Raft Disruption by Sphingomyelinase and Myriocin via Transient Receptor Potential Vanilloid 1 and Transient Receptor Potential Ankyrin 1 Ion Channel Modulation - Horváth, Ádám; Payrits, Maja; Steib, Anita; Kántás, Boglárka; Biró-Süt, Tünde; Erostyák, János; Makkai, Géza; Sághy, Éva; Helyes, Zsuzsanna; Szőke, Éva (Frontiers in Pharmacology, 2021)
Transient Receptor Potential (TRP) Vanilloid 1 and Ankyrin 1 (TRPV1, TRPA1) cation channels are expressed in nociceptive primary sensory neurons, and integratively regulate nociceptor and inflammatory functions. Lipid rafts are liquid-ordered plasma membrane microdomains rich in cholesterol, sphingomyelin and gangliosides. We earlier showed that lipid raft disruption inhibits TRPV1 and TRPA1 functions in primary sensory neuronal cultures. Here we investigated the effects of sphingomyelinase (SMase) cleaving membrane sphingomyelin and myriocin (Myr) prohibiting sphingomyelin synthesis in mouse pain models of different mechanisms. SMase (50 mU) or Myr (1mM) pretreatment significantly decreased TRPV1 activation (capsaicin)-induced nocifensive eye-wiping movements by 37% and 41%, respectively. Intraplantar pretreatment by both compounds significantly diminished TRPV1 stimulation (resiniferatoxin)-evoked thermal allodynia developing mainly by peripheral sensitization. SMase (50 mU) also decreased mechanical hyperalgesia related to both peripheral and central sensitizations. SMase (50 mU) significantly reduced TRPA1 activation (formalin)-induced acute nocifensive behaviors by 64% in the second, neurogenic inflammatory phase. Myr, but not SMase altered the plasma membrane polarity related to the cholesterol composition as shown by fluorescence spectroscopy. These are the first in vivo results showing that sphingolipids play a key role in lipid raft integrity around nociceptive TRP channels, their activation and pain sensation. It is concluded that local SMase administration might open novel perspective for analgesic therapy.